Lipase-catalyzed ring-opening copolymerization of ω-pentadecalactone and δ-valerolactone by reactive extrusion. Issue 3 (27th January 2020) - Li, Changcun; Pan, Shuaijun; Xu, Weijian; Lu, Yanbing; Wang, Peipei; Zhang, Fuming; Gross, Richard Alan
Abstract : This work demonstrates the synthesis of poly(ω-pentadecalactone- co -δ-valeroLactone) with high molecular weight ( M n = 71.3 kDa) and low polydispersity ( Đ = 1.67) within 6 hours by reactive extrusion (REX) using a lipase catalyst (Novozyme-435). Abstract : This work demonstrates the synthesis of poly(ω-pentadecalactone- co -δ-valeroLactone) with high molecular weight ( M n = 71.3 kDa) and low polydispersity ( Đ = 1.67) within 6 hours by reactive extrusion (REX) using a lipase catalyst (Novozyme-435). The catalyst under REX conditions effectively promoted transesterification with increased reaction time providing access to copolymers with blocky and nearly random sequence distributions.